Studi Pengaruh Kelembapan dan Polutan pada Kinerja Isolator Arrester 20 kV - Naufal Hilmi Fauzan; Sasongko Pramonohadi; Muhammad Ariq Achnida Syam; Rafi Ramadhana Ardiantara (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2023)
An arrester is a device that serves to protect equipment from dielectric failure caused by lightning impulses, switching surges, or voltage spikes that exceed an equipment’s dielectric capability. The majority of arresters have an event counter installed, which is used to track how frequently they have been in use. In humid and heavily polluted environmental conditions, it is very easy for surface discharge to occur on the isolator. Surface discharge is a discharge that occurs in an area directly related to a dielectric surface that has an excess electric field, thus triggering a discharge. If a surface discharge continues to happen, it can result in a flashover. Flashover that hits part of the event counter can make the event counter experience error, so it does not show the correct number. In addition, the performance of the event counter will be disrupted. For this reason, it is necessary to test the arrester insulators with three schemes: clean condition insulators, humid condition insulators, and insulators with humid and polluted conditions. In this experiment, pollutants were used with an equivalent salt deposit density (ESDD) value of 4.69 mg/cm2 and a nonsoluble deposit density (NSDD) value of 1.8841 mg/cm2. According to the experiment results, it was found that there was a decrease in the ability of arrester insulation to withstand voltage caused by humidity and pollutants. Humidity decreased breakdown voltage (BDV) by 5.8 kV for every 5% increase in humidity, while pollutants decreased BDV by 59 kV when the insulator was exposed to pollutants.